The Role of Fibrinogen-Like Protein 2 on Immunosuppression and Malignant Progression in Glioma. (26th June 2018) - Latha, Khatri; Yan, Jun; Yang, Yuhui; Gressot, Loyola V; Kong, Ling-Yuan; Manyam, Ganiraju; Ezhilarasan, Ravesanker; Wang, Qianghu; Sulman, Erik P; Eric Davis, R; Huang, Suyun; Fuller, Gregory N; et al.
Abstract: Background: Virtually all low-grade gliomas (LGGs) will progress to high-grade gliomas (HGGs), including glioblastoma, the most common malignant primary brain tumor in adults. A key regulator of immunosuppression, fibrinogen-like protein 2 (FGL2), may play an important role in the malignant transformation of LGG to HGG. We sought to determine the mechanism of FGL2 on tumor progression and to show that inhibiting FGL2 expression had a therapeutic effect. Methods: We analyzed human gliomas that had progressed from low- to high-grade for FGL2 expression. We modeled FGL2 overexpression in an immunocompetent genetically engineered mouse model to determine its effect on tumor progression. Tumors and their associated microenvironments were analyzed for their immune cell infiltration. Mice were treated with an FGL2 antibody to determine a therapeutic effect. Statistical tests were two-sided. Results: We identified increased expression of FGL2 in surgically resected tumors that progressed from low to high grade (n = 10). The Cancer Genome Atlas data showed that LGG cases with overexpression of FGL2 (n = 195) had statistically significantly shorter survival (median = 62.9 months) compared with cases with low expression (n = 325, median = 94.4 months, P < .001). In a murine glioma model, HGGs induced with FGL2 exhibited a mesenchymal phenotype and increased CD4 + forkhead box P3 (FoxP3) + Treg cells, implicating immunosuppression as a mechanism for tumor progression. Macrophages in these tumors were skewed toward the immunosuppressive M2 phenotype. Depletion of Treg cells with anti-FGL2 statistically significantly prolonged survival in mice compared with controls (n = 11 per group, median survival = 90 days vs 62 days, P = .004), shifted the phenotype from mesenchymal HGG to proneural LGG, and decreased M2 macrophage skewing. Conclusions: FGL2 facilitates glioma progression from low to high grade. Suppressing FGL2 expression holds therapeutic promise for halting malignant transformation in glioma.